2009
DOI: 10.1590/s1516-89132009000400029
|View full text |Cite
|
Sign up to set email alerts
|

Reducing COD level on oily effluent by utilizing biosurfactant-producing bacteria

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…amicalis strain DRM 190-07 was isolated from the soil contaminated with diesel oil collected near the REPLAN petroleum refinery in Campinas, São Paulo, Brazil. This strain was originally identified by morphological and biochemical analysis as Planococcus citreus strain CCT 4018 (Jacobucci et al 2001;Jacobucci et al 2009). The isolate has been subsequently reclassified as G. amicalis based on 16S rDNA sequence analysis.…”
Section: Materials and Methods 16s Sequence Analysis Of The Biosurfacmentioning
confidence: 99%
“…amicalis strain DRM 190-07 was isolated from the soil contaminated with diesel oil collected near the REPLAN petroleum refinery in Campinas, São Paulo, Brazil. This strain was originally identified by morphological and biochemical analysis as Planococcus citreus strain CCT 4018 (Jacobucci et al 2001;Jacobucci et al 2009). The isolate has been subsequently reclassified as G. amicalis based on 16S rDNA sequence analysis.…”
Section: Materials and Methods 16s Sequence Analysis Of The Biosurfacmentioning
confidence: 99%
“…Jacobucci et al (2009) describe a strain of P. agglomeras isolated from soil contaminated with oil able to grow and produce BS using kerosene as sole carbon source, what bioremediate proposed as candidate for hydrocarbon contaminated sites, it is possible that the strains isolated in this study are able to grow in hydrocarbons as sole carbon source for their ability also shown in emulsification. It described that the BS produced by Pantoea sp., Is of glycolipid type (Dewart et al, 2006, Gomes de Almeida et al, 2015, so presumably the BS produced by native strains are the glycolipids type.…”
Section: Introductionmentioning
confidence: 92%
“…Jacobucci et al (2009) describen una cepa de P. agglomeras aislada de suelos contaminado con aceite capaz de crecer y producir BS empleando keroseno como única fuente de carbono, lo que la proponen como candidata para biorremediar sitios contaminados con hidrocarburos, es posible que las cepas aisladas en este estudio sean capaces de crecer en hidrocarburos como única fuente de carbono también por su habilidad mostrada en la emulsificación. Se ha descrito que el BS producido por Pantoea sp., es de tipo glicolipido (Dewart et al, 2006;Gomes de Almeida et al, 2015), por lo que presumiblemente el BS producido por las cepas nativa sean del tipo glicolipidos.…”
Section: Introductionunclassified
“…At optimal concentration, both microbial metabolites showed simultaneous action on the availability/hydrolysis of fats, and the authors concluded that there is potential to treat wastewater from a poultry slaughterhouse and there will be no need for a flotation phase. Jacobucci et al (2009) observed, by COD reduction, the application of two bacterial species (Pantoea agglomerans and Planococcus citreus) that are biosurfactant producers and of a biosurfactant produced by them, in a greasy effluent that comes from a soap and margarine industry. The effluent presented 4,400 mg L -1 COD and 70 to 76% of removals that were obtained from COD with an application of bacterial strains and biosurfactants after 24-contact hours with the effluent.…”
Section: Anaerobic Biodegradation Of a Pretreated Effluentmentioning
confidence: 99%